Climate change increases potential plant species richness on Puerto Rican uplands - Azad Henareh Khalyani; William A. Gould; Michael J. Falkowski; Robert Muscarella; María Uriarte; Foad Yousef (Climatic Change, 2019)

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study - Mark D. Rowe; Eric J. Anderson; Henry A. Vanderploeg; Steven A. Pothoven; Ashley K. Elgin; Jia Wang; Foad Yousef (Limnology and Oceanography, 2017)
We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a ) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenarios. During the winter‐spring phytoplankton bloom, spatial patterns of Chl a were controlled by variables that influenced surface mixed layer depth: deep mixing reduced net phytoplankton growth through light limitation and by exposing the full water column to mussel filter feeding. Onset of summer and winter stratification promoted higher surface Chl a initially by increasing mean light exposure and by separating the euphotic zone from mussels. During the summer stratified period, areas of relatively high Chl a were associated with coastal plumes influenced by tributary‐derived nutrients and coastal upwelling‐downwelling. While mussels influenced spatial and temporal distribution of Chl a , lake‐wide, annual mean primary production was more sensitive to phosphorus and warm/cool meteorology scenarios than to mussel filter feeding scenarios. Although Chl a and primary production declined over the quagga mussel invasion, our results suggest that increased nutrient loads would increase lake‐wide productivity even in the presence of mussels; however, altered spatial and temporal patterns of productivity caused by mussel filter feeding would likely persist.

A plague of waterfleas (Bythotrephes): impacts on microcrustacean community structure, seasonal biomass, and secondary production in a large inland-lake complex - W. Charles Kerfoot; Martin M. Hobmeier; Foad Yousef; Brenda Moraska Lafrancois; Ryan P. Maki; Jodi K. Hirsch (Biological Invasions, 2016)

Light detection and ranging (LiDAR) and multispectral studies of disturbed Lake Superior coastal environments - W. Charles Kerfoot; Foad Yousef; Sarah A. Green; Robert Regis; Robert Shuchman; Colin N. Brooks; Mike Sayers; Bruce Sabol; Mark Graves (Limnology and Oceanography, 2012)
Due to its high spatial resolution and excellent water penetration, coastal light detection and ranging (LiDAR) coupled with multispectral imaging (MSS) has great promise for resolving shoreline features in the Great Lakes. Previous investigations in Lake Superior documented a metal‐rich “halo” around the Keweenaw Peninsula, related to past copper mining practices. Grand Traverse Bay on the Keweenaw Peninsula provides an excellent Great Lakes example of global mine discharges into coastal environments. For more than a century, waste rock migrating from shoreline tailings piles has moved along extensive stretches of coast, damming stream outlets, intercepting wetlands and recreational beaches, suppressing benthic invertebrate communities, and threatening critical fish breeding grounds. In the bay, the magnitude of the discarded wastes literally “reset the shoreline” and provided an intriguing field experiment in coastal erosion and spreading environmental effects. Employing a combination of historic aerial photography and LiDAR, we estimate the time course and mass of tailings eroded into the bay and the amount of copper that contributed to the metal‐rich halo. We also quantify underwater tailings spread across benthic substrates by using MSS imagery on spectral reflectance differences between tailings and natural sediment types, plus a depth‐correction algorithm (Lyzenga Method). We show that the coastal detail from LiDAR and MSS opens up numerous applications for ecological, ecosystem, and geological investigations.

Temperature, recreational fishing and diapause egg connections: dispersal of spiny water fleas (Bythotrephes longimanus) - W. Charles Kerfoot; Foad Yousef; Martin M. Hobmeier; Ryan P. Maki; S. Taylor Jarnagin; James H. Churchill (Biological Invasions, 2011)